Analysis of pension systems in the European Union based on cluster analysis - Havay, Dóra Anna (Public Finance Quarterly, 2025)
Sovereign pension systems in the European Union are diverse. The similar challenges facing these systems and the deepening of economic integration have made and continue to make Community objectives and recommendations necessary. In my study, I have analysed the pension systems of the EU Member States, their parametric and paradigmatic characteristics, using cluster analysis. I was looking for answers to the question of which clusters can be created if we examine the structures independently of economic and demographic indicators, and what conclusions can be drawn from this regarding the necessary restructuring of the Hungarian pension system. The results of the data reduction procedure suggest that an efficient and modern pension system is based on a multi-pillar, individual accounting system with built-in automaticity to promote its long-term sustainability, increasing the resilience of pension systems to exogenous processes and making short-term and frequent interventions unnecessary.